Evaluation of tourism websites - Bonjisse, Brito José (2017)
The aim of the paper was to identify the evaluation techniques of tourism websites in order to make future judgement analysis of websites. Although, it is difficult to make a systematic and complete evaluation on websites, they are quality due to their diversity of functionalities, which make them complex to analyses. Many studies have proposed new website evaluation frameworks and criteria. The research attempted to understand and improve website evaluation based in models related to the tourism websites. Through those models, the research proposed a new model based on the previous models discussed on this paper.The method used to the research was qualitative approach like reading journals, books, articles, interpret phenomena and virtual research by internet,and according to the findings this analysis found that websites should look on the ergonomics recommendations.